Enforcing Environmental Policy – the role of the European Union - Guterres, Iva (UNIO – EU Law Journal, 2022)
The concerns regarding climate change are on the top of government agendas worldwide, and a global response is urgently required given the climate events that countries all over the world are facing. The European Union (EU) is at the forefront, assuming the leadership in environmental policy with several legal initiatives underway, which have culminated in the promulgation of the European Climate Law and the presentation of the proposed Directive of a Carbon Border Adjustment Mechanism (CBAM). Nonetheless, the EU struggles with difficulties regarding the effectiveness of legal measures, in particular carbon leakage problems. Carbon leakage problems prevail globally as production shifts to countries with less stringent climate regulations, avoiding costs in countries with high emission charges. A resolution regarding the implementation of the CBAM was passed by the European Parliament in March 2021. On the 14th of July 2021, the EU presented 13 policy measures aiming to reduce its GHG emissions by 55% by 2030. On the 22nd of June 2022 the European Parliament voted to adopt the regulation about CBAM. As the EU has played a unique and strong role in climate policy enforcement, the aim of this article is to present this policy option, in the light of the oncoming CBAM. Therefore, the ‘EU climate club’ is imposing coercive environmental tax policies on other countries.